Eficiência nutricional da dieta de novilhos de corte mantidos em pastagem associada a suplementação - Araujo, Tiago Luís Da Ros de [UNESP] (2015)
The objective of this study was to evaluate the intake, digestibility, performance and ruminal parameters of Nellore steers in rainy and dry season. For this two experiments was conducted, the experiment 1 were evaluated three levels of supplementation (1.0, 1.5 and 2.0% of body weight (BW)) in Brachiaria brizantha cv. Marandu from September to December 2011. The experiment 2 were evaluated the effects of three heights (15, 25 and 35 cm) of pasture Brachiaria brizantha cv. Marandu associated with mineral supplementation or multiple supplement with protein and energy (0.3 or 0.6% of PC) on intake, digestibility, ruminal fermentation and metabolic parameters of Nellore steers in January to April 2013. In experiment 1 the increase supplement level in the diet caused by the replacement effect of forage supplement and the total digestible nutrients increased linearly with the increase supplement level. To dry matter digestibility was observed opposite effect, with increasing supplement level occurred linear reduction of the apparent digestibility of the dry matter. The animal performance, there was a linear increase in average daily gain (ADG) due to the increase of supplementation level, 0.778; 1.054 and 1.096 kg / day, in treatments 1.0; 1.5 and 2.0 %BW respectively. Higher ADG increased linearly carcass yield, 54.3, 55.2, and 56.0% in response to increased supplement level. It can be concluded that the increase in the supplement level reduces forage intake increases the average daily gain and carcass yield. Supplementation of 1.5% BW has increased productivity, however supplementation level of 2.0% BW has a potential increase in stocking rate due to reduced forage intake. The experiment 2 in the pastures of 15 cm animals were supplemented with multiple supplement, 0.3 and 0.6% BW, and pastures of 25 and 35 cm were used mineral mixture ad libitum and 0.3% BW multiple supplement, amounting to six treatments. 12 canullated Nellore steers ...